Differentiated Instruction Strategies to Enhance EFL Learning in A Mixed-Proficiency Seventh-Grade Classroom - Purnamaningwulan, Rina Astuti; Purwanto, Andrea Rinjani (Universitas Lancang Kuning, 2025)
In the context of EFL in Indonesian junior high schools, classrooms often comprise students with mixed proficiency levels. This poses challenges due to the heterogeneity in their initial proficiency. This study explored the practical implementation of Differentiated Instruction (DI) strategies in a seventh-grade English class with mixed competency levels and investigated students’ perceptions of the implementation in terms of its efficacy and acceptability. This study was conducted in four weeks and involved thirty-one seventh-grade students from a public Junior High School in Yogyakarta. Data were collected using a questionnaire, observation field notes, semi-structured interviews, and teaching-learning artifacts. The quantitative data were analysed descriptively, while thematic approach was employed to analyse the qualitative data. The findings showed that various DI strategies were implemented across the three learning dimensions, i.e. content, process, and product. Students generally had positive perceptions of the DI strategies as they had better learning experiences, enhanced learning motivation, and improved collaboration skills. The mean score for student satisfaction was high (M = 4.22), with product differentiation receiving the highest rating (M = 4.48). However, a concern was raised regarding the mixed-proficiency grouping. These findings suggest that carefully-designed DI strategies could enhance students’ learning experiences and minimize challenges in EFL mixed-proficiency classrooms. This study provides insights into practical implementation of DI in secondary-level EFL contexts. It also suggests that instructional practices in diverse EFL classrooms should be improved.